The competences of the creative teacher for the development of problem solving skills in the area of mathematics in District 13D03 Jipijapa-Puerto López - Chinga Medina, María Alexandra (Revista Minerva, 2023)
The teacher’s competencies allow the development of students’ skills to respond appropriately to the activities proposed by their teacher in the classroom. The objective of this work is to determine the competences of the creative teacher for the development of problem-solving skills in the area of mathematics in District 13D03Jipijapa - Puerto-López. The research was developed under a qualitative-quantitative approach, it is exploratory, descriptive and bibliographic, in addition the theoretical methods of analysis, synthesis, induction and deduction were used. The study was carried out in elementary school, through observation and a question sheet, a survey was also applied to teachers with a structured question form that was sent via Google Form. The results show that students have low knowledge about mathematical problem solving strategies, since teachers do not apply innovation in the classroom that allows them to achieve effective results through learning motivation. It is concluded that creativity is associated in the educational field itself that provides the tools for the development of abilities and skills in the teaching-learning process for resolution of the proposed activities in the classroom.